SARS-CoV-2 antibody and neutralization dynamics among persons with natural- and vaccine-induced exposures - Christopher S. Semancik; Romain Fantin; Julia Butt; Arturo Abdelnour; Viviana Loria; Carolina Porras; Amada Aparicio; Sarah S. Jackson; Roy Wong-McClure; Rebeca Ocampo; Melvin Morera; Michael Zúñiga; et al. (PLoS ONE, 2025)
Previous SARS-CoV-2 research indicates that antibody levels and corresponding neutralization potential increase with additional exposures (comprising vaccination or infection), and that hybrid immunity resulting from combined vaccination and natural infection is more robust than either alone. However, it is unclear whether or how antibody levels increase or eventually plateau with repeated exposures and how SARS-CoV-2 exposure differs by sex or other demographic factors. Research regarding the association of antibody production with neutralization potential is also limited. We conducted this analysis within the RESPIRA population-based cohort in Costa Rica to investigate relationships between antibody levels and neutralization potential at increasing exposure levels. We examined immunological profiles from systematically defined single-exposure groups (one vaccine dose or one natural infection), double-exposure groups (two vaccine doses or one vaccine dose following a natural infection), and a triple-exposure group (two vaccine doses following a natural infection). We used a S1-RBD-based serological assay for antibody level detection and a pseudovirion assay for neutralization potential quantification. Using linear regression, we compared antibody levels and pseudoneutralization geometric mean titers between exposure groups. For single exposure groups, one vaccine dose was inferior to natural infection, but a second vaccine dose was superior to natural infection. For double exposure groups, those who were vaccinated once after infection developed higher levels of antibodies and higher neutralization potential compared with those who had only two vaccine doses. We note that peak antibody levels following an exposure may plateau after two exposures while neutralization potential continues to increase with a third exposure dose. Response patterns were comparable in males and females and in sensitivity analyses stratified by age, vaccine type, and pandemic wave. These results provide evidence that SARS-CoV-2 vaccination after COVID infection provides immunological benefit and suggest neutralization potential continues to increase after a second vaccine dose despite plateauing of antibody levels.